RICE RATOON YIELD RESPONSE TO MAIN CROPS CUTTING HEIGHT IN TIDAL SWAMP USING DIRECT SEEDING SYSTEM - Evriani Mareza; Zainal Ridho Djafar; Rujito Agus Suwignyo; Andi Wijaya (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
This study was aimed to evaluate the effect of main crops harvest cutting height on the yield of rice ratoon in the tidal swamp by using direct seeding system. The experiment was conducted in Telang Sari village, District of Tanjung Lago, Banyuasin, South Sumatra Province from November 2013 to April 2014. It measured plots 4 x 5 m through a randomized block design with 5 replications. The treatment was main crops harvest cutting height of 10, 20, 30, 40 and 50 cm above the soil surface. The results showed that the effect of cutting height on rice ratoon yield depends on the condition of photosynthetic and the amount of remaining nodes on the main crops stubble as an emergence ratoon shoots. The main crops cutting height of 20-40 cm above the soil surface increased the number of productive tillers, grain weight per hill, yield per plot, ratoon ability to grow per plot, and the rice ratoon/main crops yield ratio in tidal land by using direct seeding system.